Exploring challenges in accessing primary healthcare for pregnant women in Pakistan: a qualitative descriptive study - Bushra Asif Ali Khan; Humaira Mahmood; Jawaria Mukhtar Ahmed; Bushra Anwar; Ameer Muhammad; Rawshan Jabeen (BMC Health Services Research)
Abstract Introduction Maternal and newborn mortality are critical global health concerns. Achieving Sustainable Development Goal 3.8 (SDGs), which aims to improve these outcomes, is hindered by the poor quality of care in health facilities, a significant barrier to the utilization of antenatal care (ANC) services in Pakistan. This study aimed to explore the barriers to the underutilization of ANC services in Tehsil (sub-division of a district) Hazro, Punjab, Pakistan, from the perspective of pregnant women. Method The study employed four focus group discussions (FGDs) with 36 pregnant women who had attended at least three ANC visits. Data were collected through purposive sampling and analyzed using NVivo 12, ensuring rigor through Lincoln and Guba’s guiding principles. Result The findings revealed three key themes, following the three delays model: 1. Decision to Seek Care, 2. Delay in Reaching Healthcare Facilities, and 3. Delay in Acquiring Satisfactory and Appropriate Health Care. Women often made the decision to seek care with the support of their spouse, family, and lady health workers, highlighting the importance of their decision-making autonomy. Financial constraints did not significantly hinder access to healthcare services. However, long distances, travel time, and associated costs were identified as major barriers. Most importantly, the majority of women lacked awareness of danger signs and the importance of seeking timely medical help. This issue was compounded by the unavailability of healthcare personnel, negative staff attitudes, insufficient medicines and equipment, and a lack of referral services. Conclusion This descriptive study underscores the urgent need for affordable, accessible, and responsive maternal and child healthcare. To address these barriers, stakeholders − including policymakers, public health experts, and maternal, neonatal, and child health (MNCH) providers − must prioritize MNCH initiatives and reforms. Collaborative efforts are crucial to translating MNCH policies into effective strategies at the community level.